FAKTOR FAKTOR KEPATUHAN PADA PASIEN HIPERTENSI DI MASA PANDEMI COVID-19 - Heti Rais Khasanah; Nadia Pudiarifanti (Avicenna: Jurnal Ilmiah, 2022)
Background: Hypertension is a silent killer where the symptoms are very diverse in each individual and are almost the same as other diseases. The factors that affect the compliance of hypertensive patients in taking drugs are external factors and internal factors Objective: This study aims to determine the level of compliance in hypertensive patients in consuming antihypertensive drugs at the Bengkulu City Pharmacy. Method:This study used an observational method with sampling using consetutive sampling techniques where the data taken were those that met the inclusion criteria and exclusion criteria. Data collection is carried out by questionnaire. Result: showed that from 101 research samples, the results of the level of adherence to taking medicines for hypertensive patients with the categories of Obedient 65.30%, Moderately Obedient 25.70% and Non-Compliant 8.90%.